The Years of Great Silence : the deportation, special settlement, and mobilization into the labor army of ethnic Germans in the USSR, 1941-1955 - Pohl, J. Otto, 1970- (Stuttgart : ibidem-Verlag, 2022)
"This monograph provides a detailed yet concise narrative of the history of the ethnic Germans in the Russian Empire and USSR. It starts with the settlement in the Russian Empire by German colonists in the Volga, Black Sea, and other regions in 1764, tracing their development and Tsarist state policies towards them up until 1917. After the Bolshevik Revolution, Soviet policy towards its ethnic Germans varied. It shifted from a generally favorable policy in the 1920s to a much more oppressive one in the 1930s, i.e. already before the Soviet-German war. J. Otto Pohl traces the development of Soviet repression of ethnic Germans. In particular, he focuses on the years 1941 to 1955 during which this oppression reached its peak. These years became known as "the Years of Great Silence" ("die Jahre des grossen Schweigens"). In fact, until the era of glasnost (transparency) and perestroika (rebuilding) in the late 1980s, the events that defined these years for the Soviet Germans could not be legally researched, written about, or even publicly spoken about, within the USSR."--Page 4 of cover.
Introduction -- Sources -- Literature review and historiography -- The origins of German settlements in the Russian Empire -- Ethnic Germans in the early USSR -- The deportation -- Arrival in exile in Siberia and Kazakhstan -- Fishing in the far north -- The labor army -- The special settlement regime -- Repatriated Germans -- Local Germans -- Number of excess deaths 1941-1948 -- End of the special settlement regime for Germans -- The post-Stalin Era -- Conclusion.
Includes bibliographical references (pages 275-286).
Vendor-supplied metadata.
eBooks on EBSCOhost
Keywords: Germans -- Soviet Union -- History; Deportation -- Soviet Union -- History; Forced labor -- Soviet Union -- History; Travail forcé -- URSS -- Histoire; Deportation; Forced labor; Germans; Soviet Union; History